Study Deskriptif Pembuatan Sunai Pondok Kandang Muko Muko Provinsi Bengkulu - Muhammad Widodo; Desmawardi Desmawardi; IDN. Supenida (Jurnal Musik Nusantara, 2023)
This research focuses on the traditional musical instrument called Sunai, which is a wind and melodic instrument made from telang Kapa bamboo. The study aims to explore the organology of Sunai, including the manufacturing concepts, materials, processes, and sound production techniques. A qualitative research method with an ethnomusicological approach was employed.The research reveals that Sunai making involves several stages, such as material selection, drying, cutting, and creating tone holes according to the artist's preferences. Sunai is classified as an aerophone instrument, producing sound through the air. The instrument is commonly played during public events like weddings and the annual Gandai Dance, typically performed at night after the Isha prayer and concluding before dawn. This study specifically examines Mr. Ma'rup's unique technique in making Sunai, which differentiates his instruments from those made by other artisans. The findings highlight the distinctive characteristics of Mr. Ma'rup's Sunai. The research findings contribute to a deeper understanding of Sunai as a traditional musical instrument and its significance in the cultural heritage of Bengkulu.